Evaluation of misinformation among pro-Ukrainian Latvians – the role of prior attitude, analytical thinking, and emotions - Priedols, Martins; Dimdins, Girts (Frontiers in Psychology, 2023)
In this exploratory study with a community sample (N = 115), we look at the perception of pro-Russia and pro-Ukraine misinformation, mimicking content shared by naive Facebook users, and the factors related to it among pro-Ukraine Latvians. Our results support the integrative model in the perception of misinformationwe found strong evidence of myside bias, as pro-Russia misinformation was judged to be significantly less accurate than pro-Ukraine misinformation. Analytical thinking, measured with the 7-item cognitive reflection test, was associated with lower levels of pro-Ukraine misinformation accuracy judgments and lower overall misinformation accuracy judgments; however, there was no correlation between analytical thinking and pro-Russian misinformation accuracy judgments. Pro-Ukrainian misinformation accuracy judgments were positively related to positive emotions elicited by misinformation, the level of support for Ukraine, and the participant's age. In addition, participants indicated a higher likelihood of engaging with misinformation if they came across it online and trusted the information and if it elicited positive emotions. Thus, our findings emphasise the role of one's attitude, analytical thinking, and emotions in one's perception, evaluation, and engagement with congruent and incongruent misinformation.